2007
DOI: 10.1182/blood-2006-09-046953
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of protein C inhibitor (PCI) activity by specific oxidized and negatively charged phospholipids

Abstract: Protein C inhibitor (PCI) is a serpin with affinity for heparin and phosphatidylethanolamine (PE). We analyzed the interaction of PCI with different phospholipids and their oxidized forms. PCI bound to oxidized PE (OxPE), and oxidized and unoxidized phosphatidylserine (PS) immobilized on microtiter plates and in aqueous suspension. Binding to OxPE and PS was competed by heparin, but not by the aminophospholipid-binding protein annexin V or the PCI-binding lipid retinoic acid. PS and OxPE stimulated the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…Recently, it was shown that oxidized and unoxidized phospholipids have different effects on inhibition of coagulation. 25 In our thrombin generation experiments, we observed an almost 50% reduction in thrombin generation by anti-human factor XI. Factor XI plays an important role in enhancing thrombin generation, since trace amounts of thrombin can activate factor XI to factor XIa, which then augments thrombin generation via the tenase complex.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, it was shown that oxidized and unoxidized phospholipids have different effects on inhibition of coagulation. 25 In our thrombin generation experiments, we observed an almost 50% reduction in thrombin generation by anti-human factor XI. Factor XI plays an important role in enhancing thrombin generation, since trace amounts of thrombin can activate factor XI to factor XIa, which then augments thrombin generation via the tenase complex.…”
Section: Discussionmentioning
confidence: 76%
“…A potential pH dependence may be important for the role of PCI at inflammatory sites, if PCI is targeted to sites of inflammation, as indicated by the presence of sialyl-Le a/x epitopes and by the functions of PCI in e.g. atherosclerosis and wound healing (31,32). Future investigations are required to investigate whether these findings reflect different functions of the two forms in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that PE enhances the PS-mediated sensitivity of factor VIIa-tissue factor activity (53) and induces high affinity binding sites for factor VIII on surfaces containing PS (54). Moreover, PE has been reported in tumor cell membranes (55) and is known to regulate the activation of blood coagulation by enhancing APC inhibition by PCI (50,51). It is possible that occupation of these sites by Alboserpin interferes with the inhibitory function of PCI toward APC, which displays particularly important anticoagulant and anti-inflammatory activities in vivo (7,56).…”
Section: Kinetics and Stoichiometry Of Alboserpin-fxa Interactions-mentioning
confidence: 99%
“…However, PCI was later demonstrated to interact with oxidized PE or oxidized PS but not with PC (47,51). Therefore, binding of Alboserpin to phospholipids vesicles in solution was investigated.…”
Section: Kinetics and Stoichiometry Of Alboserpin-fxa Interactions-mentioning
confidence: 99%